Reliable and Affordable Off-Grid Electricity Services for the Poor : Lessons from the World Bank Group Experience - Independent Evaluation Group (World Bank, Washington, DC, 2016)
This learning product draws upon existing IEG evaluations, project documents and analytical work relating to the World Bank Group’s (WBG’s) experience with supporting efforts towards the rapid scale up of off-grid electrification (pico-solar products, individual solar home systems, and micro and mini-grids), in client countries. The focus is on experiences geared towards efficiently and effectively integrating off-grid electrification scale-up efforts with grid rollout – within a national roadmap for achieving universal access in a given time-frame. Relevant findings and lessons are framed as strategic considerations to inform the design, development and implementation of country engagements tailored to the prevailing sector conditions and readiness; through capacity building, technical assistance, and investment lending.